2019
DOI: 10.3390/jcm8091349
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs Modulate Sjögren’s Syndrome Associated Gene Expression and Are Involved in the Pathogenesis of the Disease

Abstract: Primary Sjögren’s syndrome (pSjS) is a chronic systemic autoimmune disorder, primarily affecting exocrine glands; its pathogenesis is still unclear. Long non-coding RNAs (lncRNAs) are thought to play a role in the pathogenesis of autoimmune diseases and a comprehensive analysis of lncRNAs expression in pSjS is still lacking. To this aim, the expression of more than 540,000 human transcripts, including those ascribed to more than 50,000 lncRNAs is profiled at the same time, in a cohort of 16 peripheral blood mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 87 publications
0
18
0
Order By: Relevance
“…The expression analysis of lncRNAs in SS patients has shown lncRNAs LINC00657, LINC00511 and CTD-2020K17.1 potentially associated with the disease. These 3 lncRNAs target different genes involved in B cell physiology and malignancy, including IL15, WDR5, GNAI2, LTßR, CBX8, BAK1, BAX ext [ 60 ]. IL15 and WDR5 play an important role in B cell proliferation and differentiation; GNAI2 regulates B cell trafficking to the lymph nodes [ 61 ]; LTßR and CBX8 are involved in GC formation in inflamed tissues [ 62 , 63 ], and BAK1 and BAX are overexpressed in B cell lymphoma [ 64 ].…”
Section: Physiopathology Of Sjögren’s Syndromementioning
confidence: 99%
“…The expression analysis of lncRNAs in SS patients has shown lncRNAs LINC00657, LINC00511 and CTD-2020K17.1 potentially associated with the disease. These 3 lncRNAs target different genes involved in B cell physiology and malignancy, including IL15, WDR5, GNAI2, LTßR, CBX8, BAK1, BAX ext [ 60 ]. IL15 and WDR5 play an important role in B cell proliferation and differentiation; GNAI2 regulates B cell trafficking to the lymph nodes [ 61 ]; LTßR and CBX8 are involved in GC formation in inflamed tissues [ 62 , 63 ], and BAK1 and BAX are overexpressed in B cell lymphoma [ 64 ].…”
Section: Physiopathology Of Sjögren’s Syndromementioning
confidence: 99%
“…Epigenetic studies on the regulatory role of microRNAs and long non-coding RNAs have revealed that specific probes are significantly overexpressed in patients with pSS, and that they could assume a diagnostic role in this disorder in the near future (143)(144)(145). On the contrary, the level of other microRNAs has been found to be reduced in pSS patients with lymphoma or pre-lymphoma condition (146).…”
Section: Need For New Biological Markersmentioning
confidence: 99%
“…The transcriptome analysis of PBMCs from pSS patients and healthy controls identified 199 differentially expressed lncRNAs. Through a complex network analysis of lncRNA–miRNA–gene functional interactions, three lncRNAs, namely, LINC00657, LINC00511 and CTD-2020K17.1, were identified to be involved in the pathogenesis of pSS [ 126 ]. Recently, a study demonstrated that the lncRNA PVT1 is upregulated in the CD4 + T cells of SS patients.…”
Section: Important Roles Of Lncrnas In Autoimmune Diseasesmentioning
confidence: 99%